Immunopurification of pathological prion protein aggregates. - Emiliano Biasini; Laura Tapella; Susanna Mantovani; Matteo Stravalaci; Marco Gobbi; David A Harris; Roberto Chiesa (PLoS ONE)
Background Prion diseases are fatal neurodegenerative disorders that can arise sporadically, be genetically inherited or acquired through infection. The key event in these diseases is misfolding of the cellular prion protein (PrP(C)) into a pathogenic isoform that is rich in beta-sheet structure. This conformational change may result in the formation of PrP(Sc), the prion isoform of PrP, which propagates itself by imprinting its aberrant conformation onto PrP(C) molecules. A great deal of effort has been devoted to developing protocols for purifying PrP(Sc) for structural studies, and testing its biological properties. Most procedures rely on protease digestion, allowing efficient purification of PrP27-30, the protease-resistant core of PrP(Sc). However, protease treatment cannot be used to isolate abnormal forms of PrP lacking conventional protease resistance, such as those found in several genetic and atypical sporadic cases. Principal findings We developed a method for purifying pathological PrP molecules based on sequential centrifugation and immunoprecipitation with a monoclonal antibody selective for aggregated PrP. With this procedure we purified full-length PrP(Sc) and mutant PrP aggregates at electrophoretic homogeneity. PrP(Sc) purified from prion-infected mice was able to seed misfolding of PrP(C) in a protein misfolding cyclic amplification reaction, and mutant PrP aggregates from transgenic mice were toxic to cultured neurons. Significance The immunopurification protocol described here isolates biologically active forms of aggregated PrP. These preparations may be useful for investigating the structural and chemico-physical properties of infectious and neurotoxic PrP aggregates.